Performance of Self-compacting Concrete with Stainless Steel Slag Versus Fly Ash as Fillers: A Comparative Study - Sheen, Yeong-Nain; Le, Duc-Hien; Lam, My Ngoc-Tra (Periodica Polytechnica Civil Engineering, 2021)
Recently, stainless steel slag -a byproduct of manufacturing stainless steel is accepted as a cementitious material, the chemical characteristics of which are highly variant. This study reuses two types of stainless steel reducing slag with specific surface area of 1766 cm2/g (S1) and 7970 cm2/g (S2) in developing self-compacting concrete (SCC). Particularly, two S2-blended SCCs incorporating with S1 and fly ash as fillers (calling as S-mix and F-mix) were prepared for a comparative investigation. In both SCCs, ordinary Portland cement was replaced by S2 with various ratios (from 0 % to 50 %, increment 10 %). Testing results show that in fresh state, the F-mix exhibits higher workability and longer initial setting time than those of S-mix. In hardened state, 10 % compressive strength loss was realized as increasing S2 content up to 30 % in the both SCCs; the strength of F-mix is up to9 times of S-mix at the same rate of S2 replacement. Water absorption of the F-mix was below 3 %, suggested as a “good” quality concrete; whilst the S-mix could be longs to an “average” one. Resistivity and sulfate resistance of F-mix are considerably higher than those of S-mix. Moreover, based on the obtained data, compressive strength and electrical resistivity are correlated well with a logarithmic form.